Developing Cultural Competencies through Transnational Learning Experiences in Active Online Learning Environments - May, Dominik; Wold, Kari Anne; Moore, Stephanie L. (International Journal of Engineering Pedagogy (iJEP), 2014)
In todayâ??s world cultural competency becomes more and more important in order to act successfully in the modern economy. Nevertheless it is often difficult to engage students in immersive international experiences that develop inter-cultural awareness. Especially undergraduate engineering students have to deal with packed curricula with little or no room for languages and an often unforgiving structure that puts them a year out of course sequences if they do travel for a study abroad. In this paper, we examine how an online engineering education can be a transformational factor in this challenge. We present a joint online engineering course designed and implemented by the University of Virginia (UVa) and the TU Dortmund University (TU) with students from both countries. In addition to the course concept itself we explain our findings on student interaction throughout the course.